Carbapenems Versus Piperacillin-Tazobactam for Bloodstream Infections of Nonurinary Source Caused by Extended-Spectrum Beta-Lactamase–Producing Enterobacteriaceae. (20th May 2015) - Ofer-Friedman, Hadas; Shefler, Coral; Sharma, Sarit; Tirosh, Amit; Tal-Jasper, Ruthy; Kandipalli, Deepthi; Sharma, Shruti; Bathina, Pradeep; Kaplansky, Tamir; Maskit, Moran; Azouri, Tal; Lazarovitch, Tsilia; et al.
<x content-type="archive" xml:space="preserve">Abstract</x> A recent, frequently quoted study has suggested that for bloodstream infections (BSIs) due to extended-spectrum β-lactamase–producing Enterobacteriaceae (ESBL) Escherichia coli, treatment with β-lactam/β-lactamase inhibitors (BLBLIs) might be equivalent to treatment with carbapenems. However, the majority of BSIs originate from the urinary tract. A multicenter, multinational efficacy analysis was conducted from 2010 to 2012 to compare outcomes of patients with non-urinary ESBL BSIs who received a carbapenem (69 patients) vs those treated with piperacillin-tazobactam (10 patients). In multivariate analysis, therapy with piperacillin-tazobactam was associated with increased 90-day mortality (adjusted odds ratio, 7.9, P=.03). For ESBL BSIs of a non-urinary origin, carbapenems should be considered a superior treatment to BLBLIs. Infect Control Hosp Epidemiol 2015;36(8):981–985